1984
DOI: 10.1113/expphysiol.1984.sp002807
|View full text |Cite
|
Sign up to set email alerts
|

The Enlarged Carotid Body of the Chronically Hypoxic and Chronically Hypoxic and Hypercapnic Rat: A Morphometric Analysis

Abstract: SUMMARYRats were subjected to chronic hypoxia (10% 02) or hypoxia and hypercapnia (lO% 02 + 4% C02) for 3-4 weeks and their carotid bodies (twenty-three from twenty rats) were compared with those of litter-mate controls. Both chronic exposures, which simulated high altitude or chronic lung disease, caused a 4-10-fold increase in carotid body volume. The larger increases were attributed to higher fixation-perfusion pressures. The organs were fixed by perfusion with glutaraldehyde. Semi-thin (1 ,tm) sections for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 9 publications
3
46
0
Order By: Relevance
“…The general topographical description of the carotid bodies agreed well with that given previously (6) and is shown in Figure 1 taken from a normal animal (A) and a hypoxic animal (B). The type 1 cells of the carotid bodies of the chronically hypoxic rats showed no evidence of recent hyperplasia.…”
Section: Microvasculature Of the Carotid Bodysupporting
confidence: 69%
See 2 more Smart Citations
“…The general topographical description of the carotid bodies agreed well with that given previously (6) and is shown in Figure 1 taken from a normal animal (A) and a hypoxic animal (B). The type 1 cells of the carotid bodies of the chronically hypoxic rats showed no evidence of recent hyperplasia.…”
Section: Microvasculature Of the Carotid Bodysupporting
confidence: 69%
“…We are aware of studies (6,21) reporting changes in the morphology of type 1 cells. Even so, in random selected sections of the carotid bodies from hypoxic animals, we found that the diameter of type 1 cells fell within the normal range (16) and we did not see any evidence of mitotic spindles in type 1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rat enlargement comprises dilatation and new growth of capillaries, a 2-to 3-fold increase in the number of Type 1 cells and an increase in connective tissue and Type 2 cells (Dhillon, Barer & Walsh, 1984). In the last category we were unable to distinguish connective tissue cells from Type 2 cells with certainty.…”
mentioning
confidence: 82%
“…Various morphological changes have been reported in mammalian CB on chronic as well as on acute hypoxic exposure. CBs protect the organs from hypoxic damage by releasing neurotransmitters (NTs) and instantaneously signaling the brainstem respiratory centre via the carotid body nerve, resulting in hyperventilation that is an integral part of altitude acclimatization [2][3][4]. Currently, models of oxygen sensing are based on either a heme protein or the production of reactive oxygen species (ROS) by NAD(P)H oxidases and mitochondria [5].…”
Section: Introductionmentioning
confidence: 99%